A Sentimental Education for the Working Man : The Mexico City Penny Press, 1900-1910 - Buffington, Robert, 1952- (Book collections on Project MUSE., 2015)
Analyzing the satirical Mexico City penny press from 1900 to 1910, Robert M. Buffington argues that the press offered its working-class readers alternative masculine scripts that they could adopt to challenge social hierarchies.